2008
DOI: 10.1159/000114005
|View full text |Cite
|
Sign up to set email alerts
|

Uncomplicated Acute Renal Failure and Post-Hospital Care: A Not So Uncomplicated Illness

Abstract: Background: Although uncomplicated acute renal failure (ARF) is associated with significant hospital resource utilization, its health care requirements following hospital discharge are not well understood. The goal of this study was to characterize the post-hospital care requirements incurred by patients with uncomplicated ARF and to determine its important influencing factors. Methods: We obtained hospital case mix data sets for a 2-year period (1999–2000) from the Massachusetts Division of Health Care Financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
0
16
1
2
Order By: Relevance
“…1,[8][9][10][11][14][15][16][17] Fewer studies have reported the epidemiology of renal dysfunction in non-ICU patients. [18][19][20][21][22][23] Liangos et al 21 used the 2001 National Hospital Discharge Survey to demonstrate that 1.9% of hospitalized patients were diagnosed as having acute renal failure. Acute renal failure was assumed to be present if it was mentioned in the discharge summary and independently predicted hospital mortality and prolonged LOS.…”
mentioning
confidence: 99%
“…1,[8][9][10][11][14][15][16][17] Fewer studies have reported the epidemiology of renal dysfunction in non-ICU patients. [18][19][20][21][22][23] Liangos et al 21 used the 2001 National Hospital Discharge Survey to demonstrate that 1.9% of hospitalized patients were diagnosed as having acute renal failure. Acute renal failure was assumed to be present if it was mentioned in the discharge summary and independently predicted hospital mortality and prolonged LOS.…”
mentioning
confidence: 99%
“…Most CKD basic studies are performed with experimental models, such as the remnant model, also termed 5/6 nephrectomy (Nx), which was originally described by Shimamura and Morrison [3]. The progression of renal disease in the remnant model is characterized by the development of glomerulosclerosis and interstitial fibrosis [4,5]. The reduction of nephron mass leads to hypertrophy, hyperfiltration, glomerular and systemic hypertension, and thus, glomerulosclerosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of TLRs induces a proinflammatory cascade, with downstream participation of NF-kB target genes [5]. Furthermore, the activation of intracellular sensors such as NOD-like receptors, for example, NLRP3, leads to the formation of the inflammasome complex by converting procaspase-1 into active caspase-1, which in turn results in secretion of IL-1b, IL-18 and IL-33 [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations